Hubungan Gaya Kepemimpinan dan Gaya Komunikasi Kepala Sekolah dengan Kinerja Guru - Nurhayati, Siti; Suwandi, Suwandi (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The relationship between a leader and the leadership approach he or she applies has a very significant influence on the success of an organization or institution that he or she leads. In addition to leadership style, the importance of communication style is also a key factor. The purpose of this research is to know and understand the relationship between the leadership style and the communication style of the principal on teacher performance at MTsN 1 Jombang. Quantitative and koreanal are the types of methods of this research. It was determined that the total population was 52 teachers, then by simple random sampling technique the sample was determined to be 35 teachers. The questionnaires distributed contained 30 statements. Multiple linear regression is the form of the analytical technique used. The results of this study were obtained, namely (1) the calculated T value of 2.104 and a significance of 0.043 is evidence that leadership style has a positive and significant influence on the performance of teachers. (2) Communication style has no significant effect on teacher performance with a T-value of 1.240 and a significance of 0.224. (3) Leadership style and communication style simultaneously have a significant influence on teacher performance with a calculated F value of 2.635 and a significance of 0.087.